An Empirical Study of Workplace Violence: Ideas on How to Stop It - Walied Askarzai; Mohan Dass Mohan (AIBPM Publisher, 2019)
Zero-tolerance against Workplace Violence (WPV) should be the motto of every workplace. No worker should be a victim of such abuse. As such, organisations should ensure the existence of a safe working environment, and governments should introduce tough legislation to halt WPV. Furthermore, extensive research is required on ways to prevent WPV. The current research in this area is limited to defining WPV, finding where and when it occurs, and drafting prevention policies. But the actual way to prevent WPV remains a largely unexplored area. Brainstorming is an effective way to generate a pool of ideas on how to prevent WPV. This study generated a pool of ideas by conducting a survey on how to prevent WPV. The survey included 50 participants from various industries and found that 40% of the participants had experienced some kind WPV. This is an alarming statistic. Participants also shared their ideas on how to prevent WPV.